Association between smoking and facial wrinkling in relation with age and sex - E. Sharquie, Khalifa; R. Al-Rawi, Jamal; M. aljumaily, Maqsood (Tikrit Journal of Pharmaceutical Sciences, 2023)
There are many risk factors that accentuate wrinkling like age, sex, occupation. Smoking is a preventable risk factor of facial wrinkles formation. To test the assumption whether skin wrinkling is significantly associated with age, sex and smoking or not? A cross-sectional study was conducted in Department of Dermatology and Venereology in Baghdad teaching hospital in period from April 2011 through March 2012 on (106) respondents, Socio-demographic information and full dermatological examination was done. Facial wrinkles were examined and measured according to wrinkles score in the group. Then we simplify these score into: superficial, (I, II), medium (III, IV) and deep wrinkles (V, VI). Smoking habit was more frequent in males than females which was ststistically highly significant (P=0.001). Middle and deep wrinkles are more frequent among males while shallow wrinkles are more among females which was highly significant (P<0.001). Shallow wrinkles only appeared in second and third decades of life while middle and deep wrinkles been more frequent in forth decade of life and above which also highly significant (P<0.001). Shallow wrinkles are mostly among non smokers while middle and deep wrinkles more among smokers and ex-smokers (P<0.001). The present work had confirmed a positive association between wrinkling score and the frequency of smoking habit.